2022
DOI: 10.1002/brb3.2582
|View full text |Cite
|
Sign up to set email alerts
|

Contact patterns and costs of multiple sclerosis in the Swedish healthcare system—A population‐based quantitative study

Abstract: Background The burden of disease for persons with multiple sclerosis (MS) and society is changing due to new treatments. Knowledge about the total need for care is necessary in relation to changing needs and new service models. Objective The aim of this study was to describe the contact patterns for MS patients, calculate costs in health care, and create meaningful subgroups to analyze contact patterns. Methods All patients diagnosed with MS at Ryhov Hospital were included. All contacts in the region from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This suggests a need for more coproduced planning and design with more diverse service options and content to facilitate person‐centered care. Persons living with MS can also have other temporary or chronic conditions with treatments over a shorter or longer period in different parts of the healthcare system (Lind et al., 2022) that need coordination. These findings in the MS population is similar to the Swedish healthcare system as a whole where challenges to anticipate and respond to patients as individuals with particular needs and preferences together with inadequate coordination of care between different healthcare providers have been described (Docteur & Coulter, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests a need for more coproduced planning and design with more diverse service options and content to facilitate person‐centered care. Persons living with MS can also have other temporary or chronic conditions with treatments over a shorter or longer period in different parts of the healthcare system (Lind et al., 2022) that need coordination. These findings in the MS population is similar to the Swedish healthcare system as a whole where challenges to anticipate and respond to patients as individuals with particular needs and preferences together with inadequate coordination of care between different healthcare providers have been described (Docteur & Coulter, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within the segments, a random number sample was made where every third person received a letter with written information about the interview study along with an informed consent form. If several F I G U R E 1 Schematic of the different phases of the sampling process for the interview study, based on a former quantitative study that identified four segments of utilization of healthcare services (Lind et al, 2022).…”
Section: Recruitment and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 People with MS are often diagnosed during their working age, and the diagnosis adversely affects their earning ability, quality of life, and functional capability. 2 Caring for people with MS has enormous financial costs for health care systems, patients, and their caregivers. In the United States, the average excess direct and indirect cost of MS has been estimated at $65,612 per patient per annum (pppa).…”
mentioning
confidence: 99%
“…4 In Sweden, the median medical cost of MS is approximately $9,937 pppa. 2 The heterogeneity in cost estimates reflects different countries' medication prices and health system financing models.…”
mentioning
confidence: 99%